Knowledge of fibromialgia in Peruvian rheumatology specialists - Florian-Conder, Flavia C. (2020)
Objective: to identify knowledge levels of diagnostic criteria for fibromyalgia by Peruvian rheumatologists. Materials and methods: this is a cross-sectional descriptive study. One-hundred and fifty Peruvian rheumatologists attended the XX Peruvian Rheumatology Congress, which took place in November 22-24, 2018 in Lima, Peru. Ninety six of these 150 physicians were surveyed. A previously developed and validated questionnaire was administered to them taking into account the 2010 fibromyalgia criteria issued by the American College of Rheumatology. The statistical analysis was performed using the SPSS statistical package. Results: most rheumatologists were male (58.3%), aged 25 to 40 years (47.9%). One-third (33.3%) had more than 20 years experience, 43.8% reported that they attend rheumatology conferences once a year, 27.1% are medicine school instructors, and 40.6% declared identifying one to two new cases of fibromyalgia per year. More than half of surveyed physicians (57.3%) showed fair knowledge about fibromyalgia, more than half knew that the diagnosis for this condition is clinical, they also knew the most commonly affected age group, the frequent concomitant conditions as well as associated mental health disorders, in addition to auxiliary tests for the differential diagnosis. However, more than 90% were unaware of other diseases with similar symptoms. No significant differences were found in the level of knowledge on fibromyalgia according to age (p=0.762), sex (p=0.732) or years after qualifying (p=0.615). Conclusions: the knowledge level of diagnostic criteria for fibromyalgia by Peruvian rheumatologists is fair.